Structural study of semiconductors for photovoltaic applications (2014)
We present a study of the structural properties of Bi2S3, SnS, SnS2, SnS:Bi, Cu3BiS3 and Cu(In,Ga)Se2 (CIGS) semiconductor compounds used as absorber layer in optoelectronic devices. The samples were grown by co-evaporation processes of the metallic species on glass substrates. The effect of preparation conditions on the structural properties and chemical composition has been analyzed and made from X-ray diffraction (XRD) and Auger electron spectroscopy (AES) measurements. The results show that all compounds grow with orthorhombic structure, unlike the SnS2 and CIGS growing hexagonal and tetragonal structure, respectively. The compositional results showed that after the deconvolution of peaks associated phases Cu2Se and In2Se3 were found.